Foraminal Ligaments Tether Upper Cervical Nerve Roots: A Potential Cause of Postoperative C5 Palsy - Jack, Andrew S.; Osburn, Brooks R.; Tymchak, Zane A.; Ramey, Wyatt L.; Oskouian, Rod J.; Hart, Robert A.; Chapman, Jens R.; Jacques, Line G.; Tubbs, R. Shane (Journal of Brachial Plexus and Peripheral Nerve Injury, 2020)
Background Nerve root tethering upon dorsal spinal cord (SC) migration has been proposed as a potential mechanism for postoperative C5 palsy (C5P). To our knowledge, this is the first study to investigate this relationship by anatomically comparing C5–C6 nerve root translation before and after root untethering by cutting the cervical foraminal ligaments (FL).Objective The aim of this study is to determine if C5 root untethering through FL cutting results in increased root translation.Methods Six cadaveric dissections were performed. Nerve roots were exposed via C4–C6 corpectomies and supraclavicular brachial plexus exposure. Pins were inserted into the C5–C6 roots and adjacent foraminal tubercle. Translation was measured as the distance between pins after the SC was dorsally displaced 5 mm before and after FL cutting. Clinical feasibility of FL release was examined by comparing root translation between standard and extended (complete foraminal decompression) foraminotomies. Translation of root levels before and after FL cutting was compared by two-way repeated measures analysis of variance. Statistical significance was set at 0.05.Results Significantly more nerve root translation was observed if the FL was cut versus not-cut, p = 0.001; no difference was seen between levels, p = 0.33. Performing an extended cervical foraminotomy was technically feasible allowing complete FL release and root untethering, whereas a standard foraminotomy did not.Conclusion FL tether upper cervical nerve roots in their foramina; cutting these ligaments untethers the root and increases translation suggesting they could be harmful in the context of C5P. Further investigation is required examining the value of root untethering in the context of C5P.
Keywords: C5 palsy; ligament; nerve root; complication; foraminal stenosis; cervical decompression